BIODIVERSIDADE EM SISTEMAS AGROFLORESTAIS: AGRICULTURA SINTRÃ“PICA - Santos, Celyane Portilho; Marasca, Indiamara; Santos, Gilmar Oliveira; Diniz, Raisa Gomes; Lemos, Stella Vanucci; Solino, Antônio Jussiê da Silva (Científic@ - Multidisciplinary Journal, 2018)
The experiment aims to implement a sustainable system that will allow long - term research to evaluate the productive behavior of vegetables, fruits and trees, as well as to observe issues related to compaction and soil moisture content. Based on agroforestry implantation methodologies, agroforestry systems were adopted to allow a greater scale of production, starting with the implementation of a SAF for the production of bean (Phaseolus vulgaris), mango (Mangifera indica L), ipê (Tabebuia chrysotricha) , manioc (Manihot esculenta Crantz), banana (Musa spp.), and pumpkin (Cucurbita spp.). Forming a system with lines of alternating lines with lines of other fruit trees, timber species and fertilizers like brachiaria grass (Brachiaria decumbens), crotalaria (Crotalaria juncea L.). Cultures adopted the number of plants / spacing in the respective dimensions: ipê / 1 / 7,5x5, manioc / 1,20x1,20, mango / 1 / 7,5x5, banana / 1 / 7,5x5, beans / 2 / 5x5, pumpkin2 / 5x5. The productive behavior of vegetables: pumpkin (Cucurbita spp.). Are in development phase as well as manioc (Manihot esculenta Crantze); fruits: mango (Mangifera indica L) and banana (Musa spp.) and arboreal: ipê (Tabebuia chrysotricha) need more time to be evaluated due to their long development cycle.